Legal status of internally displaced persons in Ukraine - Tsymbalistyi, Taras; Blashchak, Anastasiia (Actual problems of law (Aktual’ni problemi pravoznavstva), 2020)
The article is devoted to the study of the theoretical and legal foundations of the legal status of internally displaced persons, the analysis of the peculiarities of their legal status, problems in the field of providing certain benefits to internally displaced persons, as well as formulation of conclusions and proposals aimed at improving the situation of internally displaced persons. As of today, the legal status of internally displaced persons does not have a sufficient level of research in modern legal science, due to the fact that Ukraine has only recently encountered this problem. Among the numerous military-political, economic, social problems that our country has faced in such a difficult and crucial time before it, the issue of resolving the fate of those people who have left their homes and were forced to flee from their own will is a special place. military actions and their humanitarian catastrophe in other regions of our country. Provision of migrants with food, shelter, minimal social and psychological assistance, at least temporary places of work, placement of children in kindergartens and schools are the main tasks that need urgent resolution. First of all, it is necessary to eliminate the very reason, but unfortunately, it is not known how long the military actions in the east of our country will last, so social services, law enforcement agencies side by side with volunteers and simply indifferent citizens are forced to take up modern humanitarian challenges. Issues related to simplifying the lives of displaced persons become important during this period. Giving them the status of internally displaced persons plays a big role. Guarantees of respect for the rights, freedoms and legitimate interests of internally displaced persons are established by the Constitution and laws of Ukraine, other normative acts, international treaties.